The Efference Copy Signal as a Key Mechanism for Consciousness - Vallortigara, Giorgio (Frontiers in Systems Neuroscience, 2021)
Animals need to distinguish sensory input caused by their own movement from sensory input which is due to stimuli in the outside world. This can be done by an efference copy mechanism, a carbon copy of the movement-command that is routed to sensory structures. Here I tried to link the mechanism of the efference copy with the idea of the philosopher Thomas Reid that the senses would have a double province, to make us feel, and to make us perceive, and that, as argued by psychologist Nicholas Humphrey, the former would identify with the signals from bodily sense organs with an internalized evaluative response, i.e., with phenomenal consciousness. I discussed a possible departure from the classical implementation of the efference copy mechanism that can effectively provide the senses with such a double province, and possibly allow us some progress in understanding the nature of consciousness.